Wide Y World: Understanding Cultures and Perspectives of Young Thai Boys’ Love Fans in the Glocalized Context - Supawantanakul, Narut (Thammasat Review, 2023)
Boys' Love (BL) media, emerging from Japan, has spread across different countries, including Thailand. Globalization has catalyzed the widespread accessibility of BL, fostering an environment wherein fans can create culturally hybridized BL cultures. Drawing on the glocalization and queer hybridization frameworks, this research analyzes the narratives of 13 young Thai BL fans. The objectives of this study were: firstly, to understand how fans engage in recreating BL cultures blending elements from both foreign and local origins, and secondly, to understand their viewpoints concerning gender and sexuality. Unlike the Thai BL of the previous two decades, which predominantly drew on Japanese influences, contemporary Thai BL blends its Japanese foundation with the Thai context and additional foreign components, particularly Korean pop culture. Culturally hybridized BL has notably heightened the visibility of male-male romance within mainstream Thai media, offering an alternative representation of sexual minorities beyond the third sex (เพศที่สาม—phet thi sam) stereotype. However, certain aspects of BL, such as the perpetuation of fixed gender roles within male-male relationships, reinforce conventional gender norms in Thai society. BL, an example of ongoing interplays of gender and sexuality concepts across varying locations and periods, expresses a complex product of these multifaceted interactions.